2021
DOI: 10.1111/dom.14488
|View full text |Cite
|
Sign up to set email alerts
|

Impact of SGLT2 inhibitors in comparison with DPP4 inhibitors on ascites and death in veterans with cirrhosis on metformin

Abstract: Sodium‐glucose cotransporter 2 inhibitors (SGLT2i) may have favourable neurohumoral and metabolic effects in patients with chronic liver disease. However, studies examining SGLT2i in this population have been limited to patients with non‐alcoholic fatty liver disease and have focused on surrogate biomarkers. Our aim was to evaluate whether SGLT2i can reduce the incidence of ascites and death over a period of 36 months in patients with cirrhosis and diabetes mellitus. Using electronic health data from Veterans … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 23 publications
1
12
0
Order By: Relevance
“…[160] In another observational study, investigators examined by propensity score-matched intention-to-treat analysis in 846 patients on metformin who subsequently received either SGLT2i or DPP-4 inhibitors. [161] Ascites was unchanged, but SGLT2i users had a reduced risk of death (adjusted HR: 0.33; 95% CI: 0.11-0.99; p < 0.05) compared with DPP-4 inhibitor users. Clearly long-term controlled studies are needed to assess the role of SGLT2i in cirrhosis.…”
Section: Pharmacotherapymentioning
confidence: 94%
“…[160] In another observational study, investigators examined by propensity score-matched intention-to-treat analysis in 846 patients on metformin who subsequently received either SGLT2i or DPP-4 inhibitors. [161] Ascites was unchanged, but SGLT2i users had a reduced risk of death (adjusted HR: 0.33; 95% CI: 0.11-0.99; p < 0.05) compared with DPP-4 inhibitor users. Clearly long-term controlled studies are needed to assess the role of SGLT2i in cirrhosis.…”
Section: Pharmacotherapymentioning
confidence: 94%
“…However, Zhang et al reported that continuation of metformin after cirrhosis diagnosis reduced the risk of mortality by 57% and no patients developed metformin‐associated lactic acidosis during follow‐up 51 . Although SGLT2 inhibitors are cleared by the liver, Saffo et al reported that SGLT2 inhibitors improved survival for patients with cirrhosis on metformin in comparison with DPP‐4 inhibitors 52 . GLP‐1As is a newer class of anti‐diabetic drugs and the use of GLP‐1As was safe and well tolerated in patients with cirrhosis, but the side effects of gastrointestinal disorders such as nausea and constipation may occur.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple studies have found that SGLT2I lowered the risk of NAFLD with pathological reductions of steatosis on histological examinations [13, 39-41]. In one study, SGLT2I reduced the risk for death and improved the survival of T2DM veterans with cirrhosis when compared to DPP4I [42]. Furthermore, SGLT2I also reduced the body mass index significantly and reduced the hepatocarcinogenesis for NAFLD [43].…”
Section: Discussionmentioning
confidence: 99%